Food Safety: The Indian Perspective - Paul, Bharat; Patel, Puja; Malik, Jasbir Singh; Gera, Vivek (National Journal of Community Medicine, 2015)
In this modern era of globalization and industrial growth, one of the key questions that need attention in a developing country like India is that of food safety. In India, the full burden of food borne illnesses is not known; most food borne illnesses go unreported. India is struggling with age old problem of poor environmental sanitation, lack of access to safe water and poor disease surveil- lance. These hazards are in addition to the menace of food adul- teration. The government of India introduced the food safety and Standards Act 2006 to overcome the deficiencies in the Prevention of food adulteration act, 1954. To achieve food safety, the public health sector must play a pivotal role in building a community of various stakeholders and partners, who share common goals and responsibilities.